2021
DOI: 10.1021/acssuschemeng.0c07422
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Pectin from Clementine Peel: A New Approach Based on Green Extracting Agents of Citric Acid/Sodium Citrate Solutions

Abstract: A new approach to extract pectin from clementine peel using citric acid/sodium citrate solutions (CSS) at different pHs as green extracting agents was proposed. In this study, the effects of extraction temperature (65–85 °C), CSS pH (2–8), and extraction time (1–3 h) on the extraction yield, uronic acid content, and degree of methyl esterification (DE) of the clementine peel pectin (CMP) were systematically evaluated by response surface methodology (RSM). Compared with traditional methods, the CMP extracted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Low-methoxyl CMPs were prepared as described in our previous study. 13 Briefly, dried clementine peel powder (10 g) was mixed with 250 mL of 0.1 M citric acid/sodium citrate solutions at pH 6 and 8, respectively. The mixtures were then placed in a shaking water bath at 65 °C for 2 h for pectin extraction.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-methoxyl CMPs were prepared as described in our previous study. 13 Briefly, dried clementine peel powder (10 g) was mixed with 250 mL of 0.1 M citric acid/sodium citrate solutions at pH 6 and 8, respectively. The mixtures were then placed in a shaking water bath at 65 °C for 2 h for pectin extraction.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…They show excellent Ca 2+ -induced gelling capacity, and the rheological behavior of their solutions is sensitive to low pH. 13 Inoculum Preparation. Three Lactobacillus strains including L. acidophilus LMG9433 T , L. casei LMG6904 T , and L. rhamnosus LMG25859 were used in this study.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral acid extraction has the characteristics of high acidity and strong corrosion, which may cause degradation of pectin and environment pollution [11]. Furthermore, the use of mineral acids may introduce toxic elements into the final products [14]. In recent years, scholars have reported that organic acids with chelating properties had the advantages of mild extraction and less degradation of pectin.…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that if acid such as citric acid and alkali such as KOH can be introduced into the acid and alkali treatments, the segment membrane can be fully removed, the improved acid and alkali processing water can be mixed without salty taste and rich in electrolytes, which has the potential to be prepared into electrolyte beverages. There have been many studies using citric acid and KOH to extract pectin from the skins and pomaces of various fruits ( He et al, 2021 , Mierczyńska et al, 2017 , Yang et al, 2018 ). The principle of segment membrane removal is to break the adhesion of pectin, cellulose and hemicellulose so that the pectin can be dissolved and the structure of the segment membrane is destroyed.…”
Section: Introductionmentioning
confidence: 99%